Reproductive rates of Nellore herd at Nhumirim farm, Nhecolândia Pantanal - 10.4025/actascianimsci.v34i1.12267 - Batista, Dayanna Schiavi do Nascimento (2011)
The pregnancy rates of nulliparous, primiparous and multiparous Nellore cows were evaluated from data from four insemination stations at a farm with extensive cow-calf system, based on native pastures typical of the Pantanal. Pregnancy probabilities were calculated by a model that included the effects of final weight, initial and final body condition scores, and average daily daily gain. The pregnancy rates were analyzed by chi-square test and statistical analyses were carried out through generalized linear models, using a binomial distribution function and the logistic regression function. The pregnancy rates were 35.28, 40.98, 74.14 and 52.00% for the 2005/2006, 2006/2007, 2007/2008 and 2008/2009 insemination stations, respectively. The nulliparous, primiparous and multiparous categories showed average pregnancy rates of 84, 43 and 47%, respectively. The effects of final weight, body condition score at the beginning of the insemination station, body condition score at the end of the insemination station and daily gain during the insemination station were significant. The probabilities of pregnancy are higher with higher final weight (except for nulliparous cows), with higher initial and final scores and higher average daily gain.